PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP MARAKNYA MAKANAN SIAP SAJI DI BANJARMASIN - Salamiah Salamiah; Muthia Septarina (Al-Adl : Jurnal Hukum, 2017)
Humans are the most perfect creature, created by God Almighty, who gives the mind and intelligence, perfected by communicating, that is the distinguishes human with the other exist in this world. Since the first, human being has a different view in assessing the foods and drinks, both related to food allowed or forbidden foods, especially for the foods that contain unhealty or danger materials. That's why the government need for legal certainty in ensuring consumer protections contained in the Act 8 of 1999 Consumer Protection.Keywords: Legal Protection, Consumer